Disordered myocardial Ca(2+) homeostasis results in substructural alterations that may promote occurrence of malignant arrhythmias - Tribulová, Narcisa; Knezl, Vladimír; Szeiffová Bačová, B; Egan Benová, Tamara; Viczenczová, C; Gonsalvesová, Eva; Slezák, Ján (Physiological research, 2016)
We aimed to determine the impact of Ca(2+)-related disorders induced in intact animal hearts on ultrastructure of the cardiomyocytes prior to occurrence of severe arrhythmias. Three types of acute experiments were performed that are known to be accompanied by disturbances in Ca(2+) handling. Langedorff-perfused rat or guinea pig hearts subjected to K(+)-deficient perfusion to induce ventricular fibrillation (VF), burst atrial pacing to induce atrial fibrillation (AF) and open chest pig heart exposed to intramyocardial noradrenaline infusion to induce ventricular tachycardia (VT). Tissue samples for electron microscopic examination were taken during basal condition, prior and during occurrence of malignant arrhythmias. Cardiomyocyte alterations preceding occurrence of arrhythmias consisted of non-uniform sarcomere shortening, disruption of myofilaments and injury of mitochondria that most likely reflected cytosolic Ca(2+) disturbances and Ca(2+) overload. These disorders were linked with non-uniform pattern of neighboring cardiomyocytes and dissociation of adhesive junctions suggesting defects in cardiac cell-to-cell coupling. Our findings identified heterogeneously distributed high [Ca(2+)](i)-induced subcellular injury of the cardiomyocytes and their junctions as a common feature prior occurrence of VT, VF or AF. In conclusion, there is a link between Ca(2+)-related disorders in contractility and coupling of the cardiomyocytes pointing out a novel paradigm implicated in development of severe arrhythmias.
Keywords: Animals; homeostáza; draslík; Potassium; Myocytes, Cardiac; noradrenalin; Homeostasis; prasata; Calcium Metabolism Disorders; Arrhythmias, Cardiac; morčata; poruchy metabolismu vápníku; Swine; krysa rodu Rattus; Guinea Pigs; zvířata; Rats; Norepinephrine; srdeční arytmie; kardiomyocyty